Training to Create Business Branding for BTPN Syariah Customers in Tambaksari District, Surabaya - Anggela Setiya Putri; Renny Oktafia (IJCS: International Journal of Community Service, 2023)
The Micro, Small and Medium Enterprises (MSME) sector has an important role in economic growth. On the other hand, the micro business sector has several advantages compared to businesses with large capacity. The advantages of this sector are its ability to absorb labor and use local resources, and its business is relatively flexible. PT Bank BTPN Syariah Tbk is a Sharia banking company that provides entrepreneurial assistance to business actors through accompanying facilitators from internship participants in the Certified Independent Study Internship (MSIB) program. The aim of this activity is to find out how to empower Micro, Small and Medium Enterprises (MSMEs) and its impact on the economic growth of BTPN Syariah customers in Tambaksari District. The method used is the ABCD (Asset Based Community Development) method, which is a community empowerment design that uses assets, with data collection techniques through observation and documentation. The results of the activities achieved show that empowering MSMEs has a positive impact on rural economic growth through increasing production, income and welfare of BTPN Syariah customers in Tambaksari District.